Interpreting the Qur’an in Javanese Islam: An Analytical Study of Tafsīr Tāj al-Muslimīn min Kalām Rabb al-‘Ālamīn by Misbah Mustafa - Supriyanto Supriyanto; Islah Gusmian; Zaenal Muttaqin (Universitas Islam Negeri Syekh Wasil Kediri, 2026)
This study aims to analyze the tradition of Javanese-language Qur’anic exegesis within the context of Islam’s development in Java, with particular attention to the interaction between Qur’anic teachings and local culture. The study positions Javanese Qur’anic tafsir not only as a reflection of Islamization as a cultural process, but also as an intellectual process that records an ongoing dialogue between religious texts and the socio-cultural realities of Javanese society. Employing a qualitative approach through textual analysis, this research examines Tafsīr Tāj al-Muslimīn min Kalām Rabb al-‘Ālamīn by Misbah Mustafa. The analysis focuses on how the tafsir accommodates local practices such as kondangan, grave visitation, and the offering of prayers for ancestors, as well as on the use of the Javanese language and the pégon script as media for Qur’anic interpretation. The findings demonstrate that Tafsīr Tāj al-Muslimīn represents an acculturative approach to Qur’anic interpretation, integrating Islamic teachings in a dialogical manner with local traditions without compromising the religion’s fundamental principles. Within this framework, the tafsir portrays Islam not as a force that eradicates local culture, but as a normative system that guides, harmonizes, and enriches local traditions through higher Qur’anic spiritual values. These findings affirm that Javanese Qur’anic exegesis constitutes a living intellectual tradition that plays a significant role in shaping a harmonious and contextually grounded form of religiosity in Java.